Anabolic exercise in haemodialysis patients: a randomised controlled pilot study. Issue 3 (8th April 2014) - Kirkman, Danielle L.; Mullins, Paul; Junglee, Naushad A.; Kumwenda, Mick; Jibani, Mahdi M.; Macdonald, Jamie H.
Abstract : Background: The anabolic response to progressive resistance exercise training (PRET) in haemodialysis patients is unclear. This pilot efficacy study aimed to determine whether high‐intensity intradialytic PRET could reverse atrophy and consequently improve strength and physical function in haemodialysis patients. A second aim was to compare any anabolic response to that of healthy participants completing the same program. Methods: In a single blind controlled study, 23 haemodialysis patients and 9 healthy individuals were randomly allocated to PRET or an attention control (SHAM) group. PRET completed high‐intensity exercise leg extensions using novel equipment. SHAM completed low‐intensity lower body stretching activities using ultra light resistance bands. Exercises were completed thrice weekly for 12 weeks, during dialysis in the haemodialysis patients. Outcomes included knee extensor muscle volume by magnetic resonance imaging, knee extensor strength by isometric dynamometer and lower body tests of physical function. Data were analysed by a per protocol method using between‐group comparisons. Results: PRET elicited a statistically and clinically significant anabolic response in haemodialysis patients (PRET—SHAM, mean difference [95 % CI]: 193[63 to 324] cm 3 ) that was very similar to the response in healthy participants (PRET—SHAM, 169[−41 to 379] cm 3 ). PRET increased strength in both haemodialysis patients and healthy participants. In contrast, PRET only enhanced lower body functional capacity in the healthy participants. Conclusions: Intradialytic PRET elicited a normal anabolic and strength response in haemodialysis patients. The lack of a change in functional capacity was surprising and warrants further investigation.